NON-FINANCIAL REPORTING IN THE CONTEXT OF EUROPEAN INTEGRATION: TRANSFORMATION, CHALLENGES AND PROSPECTS - Oksana Nesterenko; Alina Kyzym (Соціальна економіка)
The purpose of this article is to identify the key areas for further improvement of the organizational, methodological and regulatory support for the preparation and submission of non-financial reporting by Ukrainian enterprises in the context of European integration. To achieve this goal, the study provides for the solution of the following tasks: research and characterization of the methods of preparation of non-financial reporting; development of an algorithm for preparation, formation and disclosure of integrated reporting; identification of the main problems and challenges arising in the preparation of reporting in accordance with international standards and recommendations for their leveling. It is substantiated that users of accounting and reporting information today are interested not only in financial performance indicators of enterprises, but also in sustainable development as an integral part of business, which is measured mainly by non-financial indicators, which is ensured by the formation of integrated reporting.  The paper proves that the introduction of integrated reporting in Ukraine is an essential proof of the country’s integration into the global and European society, since joining the European Union not only requires fulfillment of a number of certain criteria, but also obliges the candidate country to achieve and maintain a certain level of economic, social and environmental well-being. The author develops an algorithm for preparation, formation and disclosure of integrated reporting, at each stage of which the main functions and tasks to be solved by the management apparatus are indicated. The features of the formation of integrated reporting according to the international standards of the Global Reporting Initiative and the Sustainability Accounting Standards Board are disclosed. The characteristics of a sociological survey on the prevalence of the use of reporting standards among leading companies are presented. The mechanism of joint use of GRI and SASB standards in the formation of sustainability reports is substantiated, which will allow obtaining a comprehensive characterization of corporate activities, which will disclose information on the achievement of sustainable development goals and organized financial information. Prospects for further research in the subject matter of this article are related to the development of a mechanism for improving the quality and international comparability of non-financial reporting to assess the contribution of the corporate sector to the achievement of sustainable development goals.